2008
DOI: 10.1093/toxsci/kfn136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2E1 Gene Deletion in Mice on Expression of Microsomal Epoxide Hydrolase in Response to VCD Exposure

Abstract: Females are born with a finite number of primordial follicles. 4-Vinylcyclohexene diepoxide (VCD) is a metabolite formed by epoxidation of 4-vinylcyclohexene (VCH) via its two monoepoxides 1,2- and 7,8-4-vinylcyclohexene monoepoxide (VCM). VCD specifically destroys small preantral (primordial and small primary) follicles in the rodent ovary. The phase I enzyme, cytochrome P450 isoform 2E1 (CYP2E1) is involved in ovarian metabolism of VCM to VCD. Further, microsomal epoxide hydrolase (mEH) can detoxify VCD to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…It is important to note that the ovary has the capability to biotransform chemicals to more or less toxic metabolites, and these metabolic processes are highly active in ovarian tissues Keating 2011 , 2012b ;Bhattacharya et al 2012Bhattacharya et al , 2013Igawa et al 2009 ;Keating et al 2008aKeating et al , b , 2010Madden and Keating 2014 ) and contribute to the extent of ovotoxicity observed. We have demonstrated that many genes encoding ovarian chemical biotransformation enzymes are regulated by PI3K signaling (Bhattacharya and Keating 2012b ;Bhattacharya et al 2012 ), including aryl hydrocarbon receptor ( AhR ) and nuclear erythroid-related factor ( Nrf2 ) (Bhattacharya and Keating 2012b ), transcription factors that regulate xenobiotic metabolism.…”
Section: Chemically Induced Infertility Mediatedmentioning
confidence: 99%
“…It is important to note that the ovary has the capability to biotransform chemicals to more or less toxic metabolites, and these metabolic processes are highly active in ovarian tissues Keating 2011 , 2012b ;Bhattacharya et al 2012Bhattacharya et al , 2013Igawa et al 2009 ;Keating et al 2008aKeating et al , b , 2010Madden and Keating 2014 ) and contribute to the extent of ovotoxicity observed. We have demonstrated that many genes encoding ovarian chemical biotransformation enzymes are regulated by PI3K signaling (Bhattacharya and Keating 2012b ;Bhattacharya et al 2012 ), including aryl hydrocarbon receptor ( AhR ) and nuclear erythroid-related factor ( Nrf2 ) (Bhattacharya and Keating 2012b ), transcription factors that regulate xenobiotic metabolism.…”
Section: Chemically Induced Infertility Mediatedmentioning
confidence: 99%
“…How these effects are produced is becoming better understood and detailed for a number of chemical classes discussed herein. While outside of the scope of this chapter, it is important to note that the ovary has the capability to biotransform chemicals to more or less toxic metabolites, and these metabolism processes are highly active in ovarian tissues (Igawa et al, 2009;Keating et al, 2008a;2008b;Rajapaksa et al, 2007a;Rajapaksa et al, 2007b) and contribute to the extent of ovotoxicity observed.…”
Section: Impact Of Environmental Chemical Exposures On Follicular Atrmentioning
confidence: 99%
“…Although in vitro follicle culture could be applied to study changes in follicle formation, follicle development, and ovarian physiology (Bhattacharya et al, 2013; Dutta et al, 2014; Igawa et al, 2009; Keating et al, 2008; Keating et al, 2008) in vitro follicle growth (IVFG) represents a more simple, rapid, and robust tool that can be applied to screening the effect of compounds on female reproductive function (Ahn et al, 2013; Cortvrindt and Smitz, 2002; Lenie et al, 2008; Lenie and Smitz, 2009; Peretz et al, 2012; Peretz and Flaws, 2013; Peretz et al, 2011; Peretz et al, 2013; Sun et al, 2008; Van Wemmel et al, 2005). The follicle is the functional unit of the ovary, comprised of germ cell (oocyte) and somatic cell (granulosa and theca cell) compartments (Albertini et al, 2001; Eppig et al, 2005).…”
Section: Introductionmentioning
confidence: 99%